Southern Coastal Road Construction and Inclusive Regional Economy in East Java - Nadilla, Yesy; Maryunani (Journal of Development Economic and Social Studies, 2025)
The Southern Coastal Road in East Java has been projected as an alternative redistribution route and a key factor for accelerating economic growth. Its development, which has cost considerable amount of time and investment, is expected to be a transformative policy impacting various sectors. However, there has been limited research directly examining the development policy for this road in East Java. This study aims to analyze the role of the Southern Coastal Route in fostering inclusive regional economic growth across the 8 districts crossed in East Java. The research employs Panel Data Regression with a Random Effects Model approach. The findings are as follows: (1) The Southern Coastal Route in East Java has not yet been able to drive changes in the economic base sector; (2) This road has a significant positive impact on the growth of GRDP per capita; (3) Growth of GRDP per capita significantly reduces the poverty rate; (4) However, growth of GRDP per capita significantly positive affecting the open unemployment rate, indicating other factors influence this variable. The study suggests that local governments should focus on expanding employment opportunities, reducing poverty, reducing unemployment, and promoting economic growth through targeted investments and increased capital accumulation in high-potential sectors.